TRANSFORMASI PENGUASAAN LAHAN PETANI SAYURAN DI JAWA BARAT: ANALISIS KUANTITATIF DISTRIBUSI DAN PERUBAHAN LUAS LAHAN - Rasmikayati, Elly; Fatimah, Sri; Saefudin, Bobby Rachmat (Fakultas Pertanian, Universitas Janabadra, 2024)
The growth and changes in agricultural land over the last few decades have created their own dynamics. Every year there is a transformation of agricultural land in Indonesia. Special focus on West Java, the area of critical land is increasing, especially in the districts of Bandung, Cianjur and Garut. The aim of this research is to investigate and analyze the composition of land holdings by vegetable farmers in West Java. This research uses secondary and primary data from a survey with respondents being 500 potato farmers in West Java. The data was analyzed using descriptive statistics using tables, cross-tabulation, diagrams and various graphs as data presentation tools. The results of data analysis in 2023 show that there changes on the structure of farmer land ownership. Although the majority (55.8%) of farmers still have a land area of less than 1 hectare, this has decreased by 7.8% compared to 2017. In particular, the decrease in agricultural land with an area of less than 0.5 hectares (3, 8%) is very high. On the other hand, there was an increase of 5% in farmer groups with land areas of 1 to 2 hectares. The concentration of land ownership in a small number of farmers (15%) who have land areas of more than 2 hectares, shows that there are large differences in land ownership. Although there has been an increase in land rentals, there is inequality in the area of land rentals. Keywords: Vegetable Farmers, Land Tenure, Descriptive Statistics INTISARIPertumbuhan dan perubahan lahan pertanian selama beberapa dekade terakhir menciptakan dinamika tersendiri. Setiap tahunnya terjadi transfornasi lahan pertanian di Indonesia. Fokus khusus pada Jawa Barat, luas lahan kritis semakin meningkat, terutama di kabupaten Bandung, Cianjur, dan Garut. Tujuan penelitian ini adalah untuk menyelidiki dan menganalisis komposisi luas penguasaan lahan oleh petani sayuran di Jawa Barat. Penelitian Ini menggunakan data Sekunder dan Primer dari Survey dengan responden adalah 500 petani kentang di Jawa barat , data tersebut dianalisis menggunakan Statistika deskriptif dengan alat tabel, cross-tabulasi, diagram dan bermacam grafik sebagai alat presentasi data Hasil analisis data tahun 2023 menunjukkan terjadi perubahan signifikan pada struktur kepemilikan lahan petani. Meski sebagian besar (55,8%) petani masih memiliki luas lahan kurang dari 1 hektar, namun hal ini mengalami penurunan sebesar 7,8% dibandingkan tahun 2017. Secara khusus, penurunan lahan pertanian dengan luas kurang dari 0,5 hektar (3,8%) sangat tinggi. Sebaliknya, terjadi peningkatan sebesar 5% pada kelompok tani dengan luas lahan 1 hingga 2 hektar. Konsentrasi kepemilikan lahan yang terdapat pada sejumlah kecil petani (15%) yang memiliki luas lahan lebih dari 2 hektar, menunjukkan adanya perbedaan kepemilikan lahan yang besar. Meskipun ada peningkatan dalam penyewaan lahan, terdapat ketidaksetaraan dalam luas lahan sewa. Kata Kunci : Petani Sayuran, Penguasaan Lahan, Statistika Deskriptif